Transformation yield surface of nanocrystalline NiTi shape memory alloy. (15th May 2022) - Zhang, Yanqiu; Jiang, Shuyong; Zhao, Guilong; Guo, Kairui
Highlights: Phase transformation of NiTi SMA under complex stress states is investigated by MD. Tension-compression asymmetry occurs in various aspects during phase transformation. Mechanisms of tension-compression asymmetry under complex stress states are revealed. 3D transformation yield surface of NiTi SMA under complex stress states is proposed. Abstract: Molecular dynamics (MD) simulation is used for investigating mechanical behavior and phase transformation in nanocrystalline NiTi shape memory alloy (SMA) under complex stress states, including uniaxial, biaxial and triaxial stress states. The simulation results indicate that tension-compression asymmetry occurs in terms of transformation strain, critical transformation stress, dissipation energy density, martensite variant and martensite domain. This asymmetry is mainly aroused by the fact that transformation strains under the stress states with tensile loading in the major deformation direction are larger than the counterparts under the stress states with compressive loading in the major deformation direction for most crystallographic orientations. The phase transformation stresses in complex stress states strictly comply with neither the Von Mises criterion without considering tension-compression asymmetry nor the Bouvet and Patoor criteria considering tension-compression asymmetry. Consequently, a new transformation yield criterion on the basis of Bouvet and Patoor criteria is proposed in the present work to precisely describe the transformation stress anisotropy of nanocrystalline NiTi SMA under complex stress states. Graphical abstract: Image, graphical abstract